Kewajiban Negara Untuk Menerima Bantuan Kemanusiaan Dalam Hal Terjadinya Internal Displaced Persons Dalam Perspektif Hukum Intemasional - Sri Wartini (Jurnal Hukum IUS QUIA IUSTUM, 2005)
A State as one of International law subjects has rights and obligations based on international law. One of the international obligations of a State is to assist and protect the right of IDP's in its territory. If a State is in ability and unwillingness to assist and protect the IDP's rights, it means the State has already violated its international obligation. In this condition, is the humanity assistance of international organization can be justified as an obligation that must be accepted based on international law perspective?. Consequently, the refusal to accept assistance can beclassified as a violation of international law, and it raises state responsibility.